Economic and financial analysis of cassava production in the commune of Ouèssè: towards a revaluation of this speculation - DAGBELOU, Vinablo Kodjo Dominique; ADEKAMBI , Souleymane Adéyèmi; YABI , Jacob Afouda (Revue Internationale du Chercheur, 2025)
Abstract Cassava plays a triple role as a major source of income, a guarantee for access to agricultural credit, and a food of high nutritional value. However, its production appears to be underdeveloped despite the existence of industrial processing units that can integrate it into value-added chains, with its derivate products in high demand on the national and international markets. This study aims to provide an in-depth analysis of profitability indicators and constraints related to cassava production in the commune of Ouèssè. A questionnaire was used to collect data, via Kobocollect, on a sample of 216 producers spread across six districts. Descriptive statistics and profitability indicators were the analytical tools used. The results demonstrate the economic and financial importance of cassava, with a profit margin of 404,400 FCFA/ha and an attractive benefit-cost ratio of 5.3 FCFA. However, producers face a lack of technical assistance (84%), labor (78.8%), and difficulties accessing their farms due to a lack of adequate road infrastructure (92%). These results show that the well-being of the rural population must be taken into account by decision-makers by addressing this speculation.